Analysis of the Economic Growth Gap in 2025 (Case Study of Developed Countries Vs Developing Countries) - Mhd Akbar; Ridho, Muhammad; Dio Pranata; Alfarizi; Dwita Sakuntala (Indonesian Journal of Entrepreneurship and Startups, 2025)
Economic growth disparities between developed and developing countries in 2025 remain a strategic global issue. This research aims to analyze differences in economic structures, policy stability, and access to technology between developed and developing countries. Using a qualitative descriptive approach, the study utilizes data from international institutions such as the World Bank and IMF, as well as related academic literature. The analysis is conducted comparatively using key indicators such as Gross Domestic Product (GDP), investment levels, and technological access. The results show that international trade between developing countries, such as Indonesia, and developed countries, such as Japan, offers opportunities to accelerate economic growth through technology transfer and foreign investment. However, barriers such as limited infrastructure, technological access, and complex regulations hinder exports. Policies like trade liberalization, export promotion, and improving human resources are needed to strengthen global competitiveness and boost economic growth.